Terorisme, Akhir Sejarah Santoso dan Masa Depan Teror di Indonesia - Sahrasad, Herdi; Al Chaidar, Al Chaidar (Jurnal Review Politik, 2016)
In Indonesia, to some extent, terrorism has achieved culmination with the explosion of the first Bali bombing by actors of Jamaah Islamiyah (JI) in 2001 that encourages and forces the state and society to move the building of effective measures, policies and systems of prevention with all the excesses and risks. In this regard, acts of terrorism by Santoso group with ISIS, a continuation of a series of terrorist by actors of Jamaah Islamiyah who carried out the Bali bombing. Santoso group along with his tissues and cells are already affiliated with ISIS, and that means terrorism in Indonesia has integrated itself with the world-class global terrorism. Therefore, after the death of Santoso and the end of his history, surveillance in the area where there are terrorists, should be tightened to restrict their movements